The Norton anthology of American literature - Baym, Nina. (New York : W.W. Norton & Co., 2003)
Presents hundreds of stories, novels, poems, memoirs, and other writings by important authors throughout American history.
Includes bibliographical references and index.
Adult
Keywords: American literature; American literature; United States -- Literary collections; United States -- Literary collections